2023
DOI: 10.1021/acs.analchem.3c01344
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Transition from High-Selective to High-Efficient Chiral Separations by Changing the Organic Modifier with Zwitterionic-Teicoplanin Chiral Stationary Phase

Abstract: The retention behavior of small molecules and N-protected amino acids on a zwitterionic teicoplanin chiral stationary phase (CSP), prepared on superficially porous particles (SPPs) of 2.0 μm particle diameter, has shown that efficiency and enantioselectivity, and so enantioresolution, dramatically change depending on the employed organic modifier. In particular, it was found that while methanol permits the boost of enantioselectivity and resolution of the amino acids, at the cost of efficiency, acetonitrile al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This indicates that the contribution to the intraparticle diffusivity of surface diffusion can be considered negligible, suggesting the localized nature of the adsorption process. This result is somehow expected since, from excess isotherm measurements, it has been demonstrated that a low-mobility water-rich layer covers the adsorbent surface hindering the mobility of the analyte molecules [ 7 ]. Little contributions of surface diffusion have been observed also in achiral HILIC mode [ 38 ], in chiral RP [ 13 ], chiral polar organic mode (POM) [ 10 ] and NP [ 6 ] chromatography.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…This indicates that the contribution to the intraparticle diffusivity of surface diffusion can be considered negligible, suggesting the localized nature of the adsorption process. This result is somehow expected since, from excess isotherm measurements, it has been demonstrated that a low-mobility water-rich layer covers the adsorbent surface hindering the mobility of the analyte molecules [ 7 ]. Little contributions of surface diffusion have been observed also in achiral HILIC mode [ 38 ], in chiral RP [ 13 ], chiral polar organic mode (POM) [ 10 ] and NP [ 6 ] chromatography.…”
Section: Resultsmentioning
confidence: 74%
“…This type of isotherm accounts for a bimodal energy distribution, given by two different adsorption sites: one selective (responsible for diastereomeric or enantioselective interactions) and one nonselective (where both enantiomers behave identically) [ 31 , 32 ]. For the reasons presented above it can be successfully applied to chiral separations [ 7 , 10 , 32 , 34 ]. For two competitive components, it is written as: with the saturation capacity (equal for both enantiomers) and the adsorption equilibrium (binding) constant.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The separation of racemic mixtures of chiral molecules is critically important in the pharmaceutical chemistry, life science, and agrochemical industries since the toxicity and biological behavior of enantiomers differ significantly. , Among them, the efficient separation and recognition of polar chiral molecules are particularly important in the development of drug substances and life sciences. This has promoted the development of chiral separation techniques. For enantiomer selective recognition and separation, chiral materials are critical to the process.…”
mentioning
confidence: 99%